Dimorfismo sexual da traquéia e siringe de periquito (Touist sp.) - Bottino, F. [UNESP]; Artoni, S.M.B. [UNESP]; Oliveira, D. [UNESP]; Pacheco, M.R. [UNESP]; Amoroso, L. [UNESP]; Tovar, M.C.H. [UNESP]; Sagula, A. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2007)
Investigaram-se as diferenças morfológicas da siringe do periquito Touist sp, cinco machos e cinco fêmeas. A traquéia e a siringe foram dissecadas com o auxílio de uma lupa estereoscópia e avaliaram-se o número de anéis, o comprimento da traquéia e da siringe e o comprimento e espessura do músculo traqueolateral. A traquéia do macho apresentou maior número de anéis e maior comprimento que a das fêmeas. O músculo traqueolateral dos machos é mais vigoroso e origina-se no 43º anel traqueal enquanto o das fêmeas origina-se no 30º anel traqueal e se insere no primeiro anel bronquial. A siringe do piriquito é constituída por anéis craniais, cinco nos machos e três nas fêmeas, anéis intermediários, com formato semelhante a uma bolha sulcada ventralmente, anéis caudais, quatro em ambos os sexos, e pessulo. O dimorfismo sexual está presente na morfometria da musculatura e das cartilagens, o que reflete no canto mais vigoroso dos machos.

The morphologic differences of the trachea and syrinx of five male and five female Touist sp. parakeets were studied. Trachea and syrinx were dissected with the aid of a stereoscopic magnifying glass and the number of rings, the length of trachea and syrinx were evaluated, as well as the length and thickness of the tracheolateral muscle. Trachea of male parakeets had larger amount of rings and was lengther than the female. Tracheolateral muscle of the males was more vigorous and arised in the 43rd tracheal ring while in the females it originated in the 30th tracheal and inserted in first bronchi ring. The syrinx was constituted by cranial rings (five in males and three in females), intermediate rings (resembly a bubble furrowed ventrally), caudal rings (four in both sexes) and the pessule. Sexual dimorphism directly influenced on the syrinx, concerning the morfometry of the musculature and cartilages, making males sound more vigorously.
Sexual dimorphism of the parakeet (Touist sp.) trachea and syrinx
Keywords: fowl; parakeet; syrinx; trachea; vocalization; Ave; periquito; siringe; traquéia; vocalização